Relationship Between Satisfaction and Waiting Time in Polowijen Primary Health Care Malang - Sangkot, Hartaty Sarma; Putri, Amalia Yunan; Pitoyo, Achmad Zani; Suryandari, Endang Sri Dewi Hastuti; Wijaya, Avid (Poltekkes Kemenkes Surakarta, 2026)
Background: Patient satisfaction depends on the quality of service, service waiting time, and the efforts made by officers to fulfill patient desires with the services provided. Waiting time that is too long will cause dissatisfaction with the patient. This study aims to analyze the relationship between waiting time and patient satisfaction in the outpatient registration section of the Polowijen Primary Health Care (PHC). Methods: This study used an analytic survey with a crosssectional approach. The population in this study were patients during August-October 6,214 people. The sample was calculated using the slovin formula of 100 people. The sampling technique uses quota sampling. Data analysis used the Chi-Square test. The waiting time at the Polowijen PHC registration section was > 10 minutes (not ideal) for 90 respondents (90%) and waiting time ≤ 10 minutes (ideal) for 10 respondents (10%). The level of patient satisfaction as many as 66 respondents (66%) felt very satisfied and 34 respondents (34%) felt satisfied. Results: There is no relationship between waiting time and patient satisfaction at outpatient registration at the Polowijen PHC (p Value > 0.05). Conclusion: As conclusion The waiting time obtained by patients > 10 minutes does not affect patient satisfaction. This happens because the Polowijen Health Center is the only health facility of choice for the patient, so waiting times that are not ideal do not affect patient satisfaction.